Purification of Anti-Interleukin-6 Monoclonal Antibody Using Precipitation and Immobilized Metal-Ion Affinity Chromatography - Iara Rocha Antunes Pereira Bresolin; Igor Tadeu Lazzarotto Bresolin; Adalberto Pessoa (Adsorption Science & Technology)
Monoclonal antibodies (MAbs) have been widely used in immunodiagnostic and clinical tests, whose applications require a high level of purity. As a result, several stages of purification are required in the downstream processing of MAbs. The objective of this study was to recover and purify an anti-interleukin-6 MAb from cell culture supernatant by a combined method involving precipitation and immobilized metal-ion affinity chromatography (IMAC), aiming its subsequent application in diagnostic kits. Experimental results suggest that it is possible to purify MAbs by precipitation with ammonium sulphate at 20–40% saturation, followed by adsorption on IMAC with immobilized Zn(II). The MAbs were obtained with a purity of 100% and a purification factor of 24.2, proving the feasibility of the method.